الثورة الليبية ومراحل الانتقال إلى الدولة، تحدياتها وحلولها: دراسة نقدية وتحليلية - بادي، مفتاح عبد الله إحميد (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
This study aims to shed light on the Libyan revolution of ‎February 17 and its transition periods to statehood - challenges and ‎solutions - (critical and analytical). lt also aims to demonstrate ‎reasons and motives for the revolution as well as discussing the ‎role of NATO intervention in overthrowing Gaddafi's regime. It ‎also discusses post-revolution transitional periods that started with ‎electing the General National Congress then electing the House ‎of Representatives. This study sheds light on internal and ‎external rounds of talks due to the conflict of legitimacy. It also ‎reveals the intervention role of some Arab countries in the ‎Libyan issues by supporting the conflicting parties with money ‎and weapons, as well as supporting the counter-revolution, ‎which increased the confusion in the Libyan issue. This study ‎focuses on the challenges that encounter this revolution and ‎suggests some solutions to make it successful. Research ‎methodology analytical approach, a key method as ‎well as inductive and descriptive approaches. This study ‎concludes uses by reaching important results and recommendations that ‎serve the purpose of this research, which demonstrate the ‎historical status of Libya and the main reasons of the Libyan ‎revolution, the motives of international intervention as well as ‎rounds of talks sponsored by the United Nations.‎